1997
DOI: 10.1007/s004210050183
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxyhemoglobin desaturation and pulmonary diffusing capacity during high-intensity exercise

Abstract: The purpose of this investigation was to examine if exercise-induced arterial oxyhemoglobin desaturation selectively observed in highly trained endurance athletes could be related to differences in the pulmonary diffusing capacity (DL) measured during exercise. The DL of 24 male endurance athletes was measured using a 3-s breath-hold carbon monoxide procedure (to give DLCO) at rest as well as during cycling at 60% and 90% of these previously determined VO2max. Oxyhemoglobin saturation (SaO2%) was monitored thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Powers et al (1992) have collected data between 10% and 100% O 2max and while they focussed their analysis on results obtained at O 2max , inspection of their data suggests that in many subjects a signi®cant reduction appeared at intensities as low as approximately 30% O 2max which is in agreement with the results from the present study. In searching for an explanation for the progressive hypoxaemia during incremental exercise, consideration must be given to mechanisms which have been suggested to change with intensity, such as inadequate hyperventilation (Dempsey et al 1984;Miyachi and Tabata 1992;Harms and Stager 1995;Turcotte et al 1997;Gavin et al 1998), an oxygen diusion limitation (Hammond et al 1986) and ventilation-perfusion ( A a ) mismatch Hopkins et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powers et al (1992) have collected data between 10% and 100% O 2max and while they focussed their analysis on results obtained at O 2max , inspection of their data suggests that in many subjects a signi®cant reduction appeared at intensities as low as approximately 30% O 2max which is in agreement with the results from the present study. In searching for an explanation for the progressive hypoxaemia during incremental exercise, consideration must be given to mechanisms which have been suggested to change with intensity, such as inadequate hyperventilation (Dempsey et al 1984;Miyachi and Tabata 1992;Harms and Stager 1995;Turcotte et al 1997;Gavin et al 1998), an oxygen diusion limitation (Hammond et al 1986) and ventilation-perfusion ( A a ) mismatch Hopkins et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…While several subsequent studies in endurance athletes have reported a signi®cant fall in arterial oxyhaemoglobin saturation (S a O 2 ) with exercise intensities at or close to maximal oxygen uptake ( O 2max ; Williams et al 1986;Powers et al 1992;Harms and Stager 1995) the mechanism of EIH remains uncertain. Several hypotheses have been suggested including intra-and extra-pulmonary shunts (Dempsey et al 1984;Powers et al 1992), inadequate hyperventilation (Dempsey et al 1984;Powers et al 1984;Miyachi and Tabata 1992;Harms and Stager 1995;Turcotte et al 1997; Gavin et al 1998), an oxygen diusion limitation based on low pulmonary capillary blood transit time or interstitial oedema (Dempsey et al 1982;Wagner et al 1986;Schaartzik et al 1992) and ventilation-perfusion inequalities (Torre-Bueno et al 1985;Hammond et al 1986;Wagner et al 1986;Schaartzik et al 1992;Hopkins and McKenzie 1993;Hopkins et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the increased airflow velocity carries pollutants deeper into the respiratory tract. Furthermore, pulmonary diffusion capacity has been shown to increase with exercise [3][4][5][6] ; it may therefore be postulated that the diVusion of pollutant gases increases with exercise. For several days after strenuous exercise, nasal mucociliary clearance has been shown to be impaired in long distance runners, 7 and this is possibly attributable to exposure to air pollution, as stressed by Atkinson.…”
mentioning
confidence: 99%
“…It does appear, though, that a large portion of male master athletes exhibit exercise‐induced arterial hypoxaemia (Anselme et al, 1994; Prefaut et al, 1994, 1997; Aguilaniu et al, 1995, 1998; Mucci et al, 1998; McClaran et al, 1995). In summary, exercise‐induced hypoxaemia has been reported to have a prevalence of about 50% (Powers et al, 1988), with athletes divided into those who desaturate and those who do not (Turcotte et al, 1997; Chapman et al, 1999; Sheel et al, 2000). There appears to be no difference in height, weight and lung volume between these two groups (Durand et al, 2000).…”
Section: Exercise‐induced Arterial Hypoxaemiamentioning
confidence: 99%